2010
DOI: 10.1128/jcm.01746-09
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Large Numbers of Pneumococcal Virulence Genes in Streptococci of the Mitis Group

Abstract: Seven streptococcal isolates from the mitis group were analyzed for the presence of pneumococcal gene homologues by comparative genomic hybridization studies with microarrays based on open reading frames from the genomes of Streptococcus pneumoniae TIGR4 and R6. The diversity of pneumolysin (ply) and neuraminidase A (nanA) gene sequences was explored in more detail in a collection of 14 S. pseudopneumoniae and 29 mitis group isolates, respectively. The mitis group isolates used in the microarray experiments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
81
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 46 publications
3
81
1
Order By: Relevance
“…E xact differentiation of the important pathogen Streptococcus pneumoniae and its close commensal relatives is a prerequisite for full appreciation of their clinical significance, pathogenic properties, and epidemiology both in routine clinical microbiology and in research. Although a number of phenotypic traits were previously assumed to be specific markers of S. pneumoniae, recent reports demonstrated that such properties, including optochin susceptibility, capsule production, and bile solubility, are also present in a substantial proportion of isolates of the commensal Streptococcus mitis (2,3,6,19,23,40). Moreover, the realization that clinical isolates of S. pneumoniae, e.g., many isolates from conjunctivitis, do not express a capsule (hence the term "atypical pneumococci") further emphasizes this problem (4, 7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…E xact differentiation of the important pathogen Streptococcus pneumoniae and its close commensal relatives is a prerequisite for full appreciation of their clinical significance, pathogenic properties, and epidemiology both in routine clinical microbiology and in research. Although a number of phenotypic traits were previously assumed to be specific markers of S. pneumoniae, recent reports demonstrated that such properties, including optochin susceptibility, capsule production, and bile solubility, are also present in a substantial proportion of isolates of the commensal Streptococcus mitis (2,3,6,19,23,40). Moreover, the realization that clinical isolates of S. pneumoniae, e.g., many isolates from conjunctivitis, do not express a capsule (hence the term "atypical pneumococci") further emphasizes this problem (4, 7).…”
mentioning
confidence: 99%
“…This is becoming an increasing problem due to the frequent and automated use of this procedure in clinical microbiology and in the annotation process employed in attempts to map complex microbiotas, such as in the Human Microbiome Project. Likewise, the suggested identification of clinical isolates of S. pneumoniae by detection of genes encoding regulatory proteins of capsule biosynthesis, e.g., cpsA/wzg, or putative virulence proteins such as autolysin (lytA), pneumolysin (ply), the surface protein PspA (pspA) (1, 30) is bound to result in a number of misidentifications due to the presence of homologs of these genes in a proportion of commensal streptococci (19,20,23,27,38,40).The biological explanation for the described problems is the phylogenetic history of these streptococcal species. In spite of striking differences in pathogenic potential, S. pneumoniae and S. mitis, S. pseudopneumoniae, Streptococcus oralis, Streptococcus infantis, and Streptococcus oligofermentans share an immediate common ancestor.…”
mentioning
confidence: 99%
“…Virulence factors that were once thought to be exclusive to the pneumococcus, such as pneumolysin (encoded by ply) and autolysin A (encoded by lytA), have been detected in commensal streptococcal species (18,35,49), compromising their specificity as species identification markers. The pathogenic potential of S. pseudopneumoniae (the pseudopneumococcus) has been demonstrated in a murine model (12) as well as in humans (2,18,23,24,28,40). Rapid, correct identification of this organism in the clinical setting is essential for diagnosis and for understanding its disease potential.…”
mentioning
confidence: 99%
“…Optochin sensitivity and bile solubility, the two standard pneumococcal phenotypic identification tests, have proven to be inconclusive for differentiating pneumococci from these atypical strains (3,4,9,10,17,19,20,22,27,29,32,34,38,39,49). Virulence factors that were once thought to be exclusive to the pneumococcus, such as pneumolysin (encoded by ply) and autolysin A (encoded by lytA), have been detected in commensal streptococcal species (18,35,49), compromising their specificity as species identification markers. The pathogenic potential of S. pseudopneumoniae (the pseudopneumococcus) has been demonstrated in a murine model (12) as well as in humans (2,18,23,24,28,40).…”
mentioning
confidence: 99%
“…Viridans group streptococci have been found to harbor a large number of genes originally identified as pneumococcal genes (20,21). Our assay incorporated a specific pair of primers that amplified a signature of the streptococcal autolysin gene that differentiated S. pneumoniae from nonpneumococcal isolates.…”
Section: Discussionmentioning
confidence: 99%